2015
DOI: 10.1007/s11010-015-2353-y
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous oral and inhalational intake of molecular hydrogen additively suppresses signaling pathways in rodents

Abstract: Molecular hydrogen (H2) is an agent with potential applications in oxidative stress-related and/or inflammatory disorders. H2 is usually administered by inhaling H2-containing air (HCA) or by oral intake of H2-rich water (HRW). Despite mounting evidence, the molecular mechanism underlying the therapeutic effects and the optimal method of H2 administration remain unclear. Here, we investigated whether H2 affects signaling pathways and gene expression in a dosage- or dose regimen-dependent manner. We first exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 29 publications
1
38
0
Order By: Relevance
“…In humans given H2-rich water orally, the H2 concentration in exhaled air reached a peak at approximately 10 min and returned to baseline 1 h after intake. 8,28, 29 In sum, past and present findings indicate that although the increase in H2 in the body is transient, its 24 h; that is, after H2 had disappeared from the medium. No significant difference was noted in Sirt1 activity between cells cultured in the presence and absence of H2 for 48 h, as was the case for the NAD + /NADH ratio.…”
Section: Discussionsupporting
confidence: 55%
“…In humans given H2-rich water orally, the H2 concentration in exhaled air reached a peak at approximately 10 min and returned to baseline 1 h after intake. 8,28, 29 In sum, past and present findings indicate that although the increase in H2 in the body is transient, its 24 h; that is, after H2 had disappeared from the medium. No significant difference was noted in Sirt1 activity between cells cultured in the presence and absence of H2 for 48 h, as was the case for the NAD + /NADH ratio.…”
Section: Discussionsupporting
confidence: 55%
“…H 2 has been reported to inhibit mitogen-activated protein (MAP) kinase signaling in cell lines and rodent disease models345. A previous report shows that inhibition of JNK, but not of ERK or p38 MAP kinase, decreases Wnt3a-induced β-catenin accumulation18.…”
Section: Resultsmentioning
confidence: 99%
“…H 2 was first reported to be a selective scavenger of • OH and peroxynitrite2. Cumulative evidence, however, suggests that H 2 functions as a signaling modulator345. In this study, we dissected the effects of H 2 on Wnt/β-catenin signaling.…”
mentioning
confidence: 98%
“…The data, obtained from human histocytic lymphoma U937 cells, indicated that H 2 O 2 and ·OH could activate PI3K-Akt and PLC-Ras-Raf-ERK signaling pathways [78], whereas Xu and Zhang discovered that saturated HS decreased LPS-induced ERK phosphorylation in a rat model of acute liver dysfunction [79]. Moreover, Sobue et al indicated that H 2 can attenuate ERK, p38 MAPK, and NF-κB activation in mouse livers [80]. Taken together, we suggested H 2 may inhibit NF-κB activation by reducing oxidative radicals-induced ERK phosphorylation, which allows degradation of IκBα from NF-κB.…”
Section: Discussionmentioning
confidence: 99%